SCIENTIFIC ASSESSMENT OF MORPHOFUNCTIONAL CHANGES IN PULMONARY MICROANGIOPATHY IN DIABETES (World Bulletin of Public Health, 2023)
This article presents a comprehensive scientific assessment of morphofunctional changes in pulmonary microangiopathy associated with diabetes. Pulmonary microangiopathy refers to alterations in the small blood vessels of the lungs, and its correlation with diabetes has gained increasing attention due to its potential impact on respiratory function and overall health. Through a systematic examination of histological and functional changes, this study aims to elucidate the intricate relationship between diabetes and pulmonary microangiopathy. The research employs advanced imaging techniques, histopathological analysis, and functional assessments to provide a nuanced understanding of the structural and physiological modifications occurring in the pulmonary microvasculature in diabetic conditions. The findings contribute to our knowledge of diabetic complications and may have implications for the development of targeted therapeutic interventions to mitigate pulmonary complications in individuals with diabetes
Keywords: Diabetes; Pulmonary Microangiopathy; Histological Changes